RESPONS PERTUMBUHAN BIBIT KARET (Hevea brasiliensis Muell.Arg) SATU PAYUNG KLON PB 260 TERHADAP PEMBERIAN DECANTER SOLID PADA MEDIA TANAH BEKAS TAMBANG BATU BARA DI POLYBAG - akhir sabri harahap; Sarman sarman; Rinaldi Rinaldi (Jambi University, Fakultas Pertanian, Program Studi Agroekoteknologi, 2018)
The management of the umbrella rubber plant of a clone PB 260 in the former mine is considered to be one of the main alternative solutions to overcome the unproductive lands with the provision of a solid decanter. This research was conducted at Teaching and Research Farm Faculty of Agriculture, University of Jambi from June to September 2017 with the aim to know the best decanter dose of rubber seed growth on the former land of coal mine in polybag. This research used a Completely Randomized Design (RAL) with 6 levels of treatment (a0) Without the solid decanter, (a1) 400 g/polybag, (a2) 500 g/polybag, (a3) 600 g/polybag, (a4) 700 g/polybag, (a5) 800 g/polybag. Each treatment consisted of 4 replications, and each replication consisted of 4 plants and 2 plants used as samples.Based on the result of this research, it can be concluded that the provision of solid decanter to the growth of rubber seedlings (Hevea brasiliensis Muell. Arg) one umbrella with soil media used for coal mining area gives better growth to diameter, number of leaf, dry weight of crown, and root dry weight than seed rubber without a solid decanter and generally a solid decanter treatment with a dose of 500 g / polybag showed improved rubber seed growth better than other treatments. Keyword: rubber seedlings the first umbrella,coal mine, solid decanter.